Characterizing anterior and posterior circulation strokes using high-resolution magnetic resonance imaging - Hongshan Chu; Shibo Dong; Yuan Zhang; Hongyu Hao; Ruisheng Duan; Xing Xing; Nan Yin; Jin An; Ya Gao; Xiangjian Xiao (SLAS Technology)
Background and Purpose: High-resolution magnetic resonance imaging (HR-MRI) is increasingly used to assess intracranial atherosclerosis (ICAS). The risks for anterior circulation stroke (ACS) and posterior circulation stroke (PCS) differ, and understanding the factors influencing these differences is important for better clinical management. This study investigates the impact of clinical risk factors on ICAS features in ACS and PCS using HR-MRI, focusing on arterial remodeling patterns. Methods: This retrospective, cross-sectional study uses HR-MRI to investigate the differences in plaque characteristics and remodeling patterns between anterior and posterior circulation strokes (ACS and PCS). Consecutive patients with acute ischemic stroke or transient ischemic attack (TIA) who received HR-MRI from January 2021 to August 2022 were enrolled. We compared ACS and PCS cases, analyzed clinical and radiological features, and examined factors associated with arterial remodeling patterns. Results: Of 208 patients, 123 had ACS, and 85 had PCS. PCS was significantly associated with diabetes (P = 0.036) and positive remodeling (P = 0.01). Differences in HbA1c, fibrinogen levels, and plaque enhancement were observed between ACS and PCS (P < 0.001; P = 0.033; P = 0.03). Multivariable analysis identified smoking (P = 0.048; OR: 1.96, 95 % CI: 1.01–3.81) and uric acid levels (P = 0.022; OR: 0.996, 95 % CI: 0.993–0.999) as independent factors associated with non-positive remodeling. Conclusions: HR-MRI reveals significant differences in risk factors and plaque characteristics between ACS and PCS, with smoking and uric acid levels associated with non-positive remodeling. These findings highlight the importance of HR-MRI in identifying plaque vulnerability and guiding clinical interventions.